Psychopathological differences among three groups of school children affected by the war in Croatia - Šikić, Neven (Array, 1997)
The consequences of extreme violence such as war torture affect children in different ways and may immediately manifest at the physical and/or psychological level, or may remain hidden and unrecognized for years. The victims are usually very reluctant to speak about their traumatic experiences, and try to deny the existence of psychological disturbances. They often seek help for somatic problems. Taking these physical complaints seriously helps to progressively reach the psychological effects of violence. Therefore, identification of these children should be directed to complete evaluation of their symptomatology and functioning. This can be done by: a) individual evaluation to get enough information on the historical events, functioning and symptoms of these children ; and b) standardized instruments which may allow the children to disclose more about their psychological experiences during the war. In this study rating scales and assessment instruments for children aged <15, such as CPRS with General Scoring Sheet (Fish, 1985) were used to assess the broad spectrum of psychopathology in this age group. These questionnaires were used in a large group of school children (N= 1888), 989 girls and 899 boys aged 7-16 years. The sample was divided into 3 groups: 843 non-displaced, 377 displaced and 669 refugee children. Results of statistical analysis (arithmetical mean and standard deviation of discriminative variables transformed in Z-values with F-ratio) showed the three groups of children (non-displaced, displaced and refugees) to significantly differ in 13 out of 15 psychopathological clusters Discriminative canonic analysis of the 3 groups of children (non-displaced, displaced and refugees) also showed significant differences. The first discriminative function (80, 24% of total variance) indicated depression, violence and antisocial behavior to be rare in non-displaced children, more pronounced in displaced, and most pronounced in refugee children. The second discriminative function (19, 67% of total variance) showed hyperactivity, anxiety and psychosomatic disturbances to be rare in non-displaced children, more frequent in refugee, and most expressed in displaced children. According to the results, the authors concluded that war id very painful for a large group of children, among whom the displaced and refugee children are most affected by psychopathologic disturbances.